Persepsi Mahasiswa Pendidikan Kewarganegaran Universitas Tadulako terhadap Perkuliahan Online di Masa Pandemi Covid 19 - Alri Lande (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2020)
This study aims to find out students' perception of online lectures, to find out the forms of application used in online lectures and to find out the supporting factors and inhibitory factors in online lectures. This research was conducted by descriptive survey research method, the sample in this study was a student of Citizenship Education semester 4 of the Department of Social Sciences Education FKIP Tadulako University. Data collection techniques using interviews and questionnaires. The findings in this study are a common place for lectures from 60 students as many as 53 or 88.3% who answered at home, as many as 2 students or 3.3% who answered in the garden and as many as 5 students or 8.3% who answered at home family or neighbors who are good internet network. Students use electronic devices to attend online lectures are gadgets and laptops. Applications that are liked in online lectures, as many as 56 students or 91.8% of students choose zoom application, as many as 4 students or 6.5% of students choose LMS application and as many as 1 student or 1.6% of students choose whatsapp application. When asked to students how far the material submitted through online lectures you can understand by students as many as 3 students answered very understandable, as many as 25 students answered understood, as many as 30 students answered sometimes understood and as many as 3 students served not understood. Students by extension or 100% choose face-to-face lectures compared to online lectures.